2008
DOI: 10.3386/w14275
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch in Law School

Abstract: An important criticism of race-based higher education admission preferences is that they may hurt minority students who attend more selective schools than they would in the absence of such preferences. We categorize the non-experimental research designs available for the study of so-called "mismatch" effects and evaluate the likely biases in each. We select two comparisons and use them to examine mismatch effects in law school. We find no evidence of mismatch effects on any students' employment outcomes or on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
3
27
0
5
Order By: Relevance
“…They contrast with causal evidence that access to higher education in general and more selective higher education in particular flattens SES gradients in income at lower points in the selectivity and income distributions (Zimmerman 2014, Dale andKrueger 2014). I find no evidence of mismatch: admission to elite business programs does not lead to poorer long-run outcomes for low-SES individuals (Sander 2004, Rothstein and Yoon 2008, Arcidiacono and Lovenheim 2016, Dillon and Smith 2017.…”
mentioning
confidence: 90%
“…They contrast with causal evidence that access to higher education in general and more selective higher education in particular flattens SES gradients in income at lower points in the selectivity and income distributions (Zimmerman 2014, Dale andKrueger 2014). I find no evidence of mismatch: admission to elite business programs does not lead to poorer long-run outcomes for low-SES individuals (Sander 2004, Rothstein and Yoon 2008, Arcidiacono and Lovenheim 2016, Dillon and Smith 2017.…”
mentioning
confidence: 90%
“…of the minority students enrolled in elite universities relative to the corresponding counterfactual outcome when these minority students attend less selective universities. As well summarized in Rothstein and Yoon (2008), the papers differ in how the counterfactual outcomes are assessed. For example, Sander (2004) first used a comparison of black and white students with the same observable credentials, who typically attend different law schools because of affirmative action, to estimate a negative effect of selectivity on law school grades; he then included both selectivity and grades in a regression for graduation and bar passage where he found that both selectivity and grades have positive coefficient, with the latter much larger than the former.…”
Section: Mismatch Literaturementioning
confidence: 99%
“…Finally, Rothstein and Yoon (2008) used both the selective-unselective and the black-white comparisons to provide bounds for the mismatch effect in law school. They find no evidence of mismatch effects on any students' employment outcomes or on the graduation or bar passage rates of black students with moderate or strong entering credentials, a group that makes up 25% of the sample.…”
Section: Mismatch Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…As argued above, bar outcomes conditional on taking the test are the best outcome measures available in the BPS to measure educational achievement. 6 In an unpublished paper, Yoon and Rothstein (2008a), who focus on blacks, also provide two direct tests of the mismatch hypothesis, one that they argue is biased against a finding of mismatch and the other that they argue is biased toward a finding of mismatch. Their first test, in the spirit of Ayres and Brooks, looks to see whether going to a more selective school while controlling for entering credentials, harms blacks.…”
Section: Review Of the Literature On Law School Mismatchmentioning
confidence: 99%